Photopatterning: On‐Demand Wrinkling Patterns in Thin Metal Films Generated from Self‐Assembling Liquid Crystals (Adv. Funct. Mater. 9/2015). (March 2015) - de Haan, Laurens T.; Leclère, Philippe; Damman, Pascal; Schenning, Albertus P. H. J.; Debije, Michael G.
Abstract : Unique wrinkling patterns with oscillating amplitudes in any arbitrarily complex fashion are generated by M. G. Debije and team on page 1360 by controlling the alignment director of a liquid crystal network using photoalignment layers in combination with photomasks. The wrinkled gold surfaces are strikingly visual which is interesting for applications ranging from diffractive elements to fine jewelry.